Kajian Yuridis Pasal 43a dalam Perubahan Undang-Undang Nomor 5 Tahun 2018 tentang Tindak Pidana Terorisme dalam Kebijakan Pre-Emtif Straight (LITERATUS, 2023)
Finding out the effects of terrorist activities in Indonesia and the application of Law Number 5 of 2018 concerning Criminal activities of Terrorism Article 43A Against Strike Pre-Emptive Policies are the goals of the research. The research approach used is normative juridical, meaning that it is based on the primary legal literature and is carried out by looking at relevant laws, regulations, theories, and conceptions. Examining Law Number 5 of 2018 concerning Amendments to Law 15 of 2003 concerning the Eradication of Criminal Acts of Terrorism is the goal of the study. The amendment to Article 43A, which inserts and reads in the framework of dealing with Criminal Acts of Terrorism, contains dangerous articles. It is unclear what is meant by countermeasures, every certain person, allegedly brought or placed and a certain place. These are the results of the discussion in Law Number 5 of 2018 concerning Amendments to Law 15 of 2003 concerning the Eradication of Criminal Acts of Terrorism. None of these arrangements can be found in the current Indonesian criminal procedural law. The conclusion is that acts of terrorism have a significant impact on the community. They are not things, but rather frequent victims of Second Life. The preceding text makes it evident how many lives were lost in the blast. These fresh impacts originate from people's personal experiences. Acts of terrorism on a larger scale actually have an impact on many things, and that is a matter of life and death for people and the nation. This loss and threat can be explained from seven aspects/fields, namely defense and security, ideology, politics, economy, society, education, and religious relations. Related to article 43A regarding the prevention of Terrorism Crime, pre-emptive efforts are needed.